Rekontemplasi Periodisasi Prasejarah Di Indonesia - Jarwo Susetyo Edi Yuwono (Balai Arkeologi Yogyakarta, 1995)
This paper is written to provide material for reflections on the prehistoric periodization system in Indonesia. Some of the main questions that become material for reflection are: whether the basis used to create the periodization system is in accordance with the objectives to be achieved; whether the periodization system is able to provide alternative solutions to various prehistoric phenomena in Indonesia; whether the periodization system can identify the process of cultural change; and finally, whether the current periodization system is still relevant with the rapid development of archaeological methods and theories. These kinds of questions are urgent for further study.